Environmental Management Accounting and Green Innovation on Financial Performance: The Moderating Role of Regulatory Pressure - Amalia Indah Fitriana; Febrianto, Hendra Galuh; Andi Kusuma Negara; Januar Eky Pambudi; Mikail Kartaloğlu (Universitas Muhammadiyah Surakarta, 2025)
This study examines the influence of Environmental Management Accounting (EMA) and Green Innovation (GI) on financial performance, with Regulatory Pressure (RP) serving as a moderating variable. Data from 150 manufacturing firms in Indonesia (2020–2025) reveal that both EMA and GI significantly enhance Return on Assets (ROA), affirming their strategic role beyond compliance. Moderation analysis further reveals that RP strengthens the positive relationship between EMA and ROA, as well as between GI and ROA, suggesting that external regulatory forces serve as institutional catalysts that enhance the effectiveness of sustainability practices. The findings contribute to Institutional Theory and Resource-Based View by demonstrating how regulatory mechanisms reinforce the strategic value of internal capabilities. Practically, this study provides insights for managers and policymakers to design regulatory frameworks that not only enforce compliance but also incentivise green transformation through digitalisation and strategic partnerships. While the study is limited to Indonesian manufacturing firms, it opens up avenues for cross-sectoral and cross-country research that incorporates qualitative dimensions and mediating variables. Overall, this research underscores the importance of aligning internal sustainability strategies with external regulatory contexts to optimise financial outcomes.